Risk Factors of Aseptic Loosening After Total Hip Arthroplasty With Collum Femoris Preserving Stem: A Long‐Term Follow‐Up Study - Yongbo Ma; Yansong Liu; Zeming Liu; Jiangqi Chang; Mengnan Li; Tao Wu (Orthopaedic Surgery)
ABSTRACT Objective The Collum Femoris Preserving (CFP) stem offers biomechanical advantages in total hip arthroplasty (THA). However, aseptic loosening remains the most common cause of failure and other severe complications, with specific risk factors associated with the CFP stem remaining inadequately defined. This study aims to investigate the possible factors associated with aseptic loosening. Methods This study retrospectively analyzed patients who underwent primary THA with the CFP stem from January 2004 to December 2009 in our institution. Patients were divided into two groups based on whether there was aseptic loosening. Demographic and imaging parameters were collected from medical records and the hospital's Picture Archiving and Communication System (PACS). Comparative analyses were conducted, and variables with significant differences were subjected to Cox regression to identify independent risk factors of aseptic loosening. Results A total of 469 hips were included, with 52 hips (11.1%) of aseptic loosening identified. Seven independent risk (protective) factors were found, including ceramic‐on‐polyethylene (COP) bearing surfaces (Hazard Ratio = 2.084, 95% Confidence Interval: 1.043–4.166, p = 0.038), history of steroid therapy (HR = 2.393, 95% CI: 1.056–5.425, p = 0.037), neck resorption ratio (NRR) (HR = 1.019, 95% CI: 1.005–1.033, p = 0.008), bone mineral density (BMD) (HR = 0.933, 95% CI: 0.891–0.976, p = 0.003), canal fill ratio (CFR) (HR = 0.951, 95% CI: 0.923–0.980, p = 0.001), cortical index (HR = 0.933, 95% CI: 0.891–0.976, p = 0.003), and varus/valgus angle between 3° and 6° (HR = 4.427, 95% CI: 2.303–8.509, p < 0.001), varus/valgus angles > 6° (HR = 8.854, 95% CI: 3.704–21.165, p < 0.001). Conclusion This study identifies key risk factors contributing to aseptic loosening, including COP bearing surfaces, steroid therapy history, excessive femoral neck resorption, and significant varus/valgus malalignment. Conversely, higher BMD, improved cortical index, and favorable CFR were protective against loosening. These findings underscore the need for careful preoperative assessment and precise intraoperative positioning to optimize long‐term implant stability.